A new species of Streptocephalus (Crustacea: Anostraca: Streptocephalidae) from the Western Ghats, India, with a key to the Asian species - Rogers, D. Christopher; Padhye, Sameer (Zootaxa, 2014)
We present and describe the fairy shrimp Streptocephalus sahyadriensis sp. nov. from the Western Ghats of India. This species is most similar to S. simplex Gurney, 1906 and S. dichotomus Baird, 1860 sharing similar basic antennal appendage morphology. However, S. sahyadriensis sp. nov. differs in the form of the ornamentation on the peduncle and the arrangement and form of spines on the antennal appendage. The three species also have different egg surface morphologies. The Asian species of Streptocephalus are discussed and a key to species is provided.